The effectiveness and sustainability of entrepreneurship trainings to SMES: The case study 0f Small Industries Development Organization (SIDO)-Tabora - Simplis, Msoffe Justin (Mzumbe University, 2024)
A thesis submitted to school of business as a partial fulfillment of the requirements for the award of Master of Business Administration (Corporate Management) Degree of Mzumbe University.